An Interdisciplinary Approach for Compulsive Behavior in Dogs: A Case Report - d'Angelo, Danila; Sacchettino, Luigi; Carpentieri, Rosanna; Avallone, Luigi; Gatta, Claudia; Napolitano, Francesco (Frontiers in Veterinary Science, 2022)
Compulsive disorder is a debilitating condition affecting both humans and animals, characterized by intrusive thoughts and recurring out-of-place behaviors. Among them, tail chasing might represent one of the most common traits in compulsive dogs. Herein, we reported the case of a 7-year-old intact male German Shepherd mixed-breed dog, presenting with tail chasing behavior. He underwent a first behavioral evaluation 1 year before (at the age of 6), when he injured himself with severe wounds at level of the tail and left thigh. To avoid any specific suffering and increase his physical health, of course, the study was carried out through an interdisciplinary approach, employing a veterinary behaviorist and a rehabilitating dog instructor. Three months after pharmacological treatment with fluoxetine and α-s1 casozepine, associated with a behavioral recovery program, the owner reported an improvement of compulsive events in his dog, in terms of intensity and frequency. Interestingly, over the following 3 months, the dog did not experience any new tail chasing episodes.